Optimization of Methodological Support of Application Tax Benefits in Regions: Practice of Perm Region - Tatarkin, Alexandr Ivanovich; Maksimov, Andrey Dmitrievich; Maksimov, Timophey Andreyevich (Economy of Regions, 2015)
In the article, the problem of the methodological process support of regional tax benefits is reviewed. The method of tax benefits assessment, accepted in Perm Region, was chosen as an analysis object because the relatively long period of application of benefits has allowed to build enough statistics base. In the article, the reliability of budget, economic, investment, and social effectiveness assessments of application benefits, based on the Method, is investigated. The suggestions of its perfection are formulated.